Glycine transporter GlyT1, but not GlyT2, is expressed in rat dorsal root ganglion–Possible implications for neuropathic pain - Schloesser, Lukas; Barthel, Franziska; Brandenburger, Timo; Neumann, Elena; Bauer, Inge; Eulenburg, Volker; Werdehausen, Robert; Hermanns, Henning (Neuroscience Letters, 2015)
Glycinergic inhibitory neurotransmission plays a pivotal role in the development of neuropathic pain. The glycine concentration in the synaptic cleft is controlled by the glycine transporters GlyT1 and GlyT2. GlyT1 is expressed throughout the central nervous system, while GlyT2 is exclusively located in glycinergic neurons. Aim of the present study was to investigate whether GlyTs are also expressed in the peripheral sensory nervous system and whether their expression is modulated in experimental neuropathic pain. Neuropathic pain was induced in male Wistar rats by Chronic Constriction Injury (CCI) and verified by assessment of mechanical allodynia (von Frey method). Expression patterns of GlyTs and the glycine binding subunit NR1 of the N-methyl-d-aspartate (NMDA) receptor in the spinal cord and dorsal root ganglia (DRG) were analyzed by Western blot analysis, PCR and immunohistochemistry. While both GlyT1 and GlyT2 were detected in the spinal cord, only GlyT1, but not GlyT2, was detected in DRG. Immunofluorescence revealed a strictly neuronal localization of GlyT1 and a co-localization of GlyT1 and NR1 in DRG. Compared to sham procedure, spinal cord and DRG expression of GlyT1 was not altered and NR1 was unchanged in DRG 12 days after CCI. GlyT1, but not GlyT2, is expressed in the peripheral sensory nervous system. The co-expression of GlyT1 and NMDA receptors in DRG suggests that GlyT1 regulates glycine concentration at the glycine binding site of the NMDA receptor. Differential regulation of GlyT1 expression in the spinal cord or DRG, however, does not seem to be associated with the development of neuropathic pain.
EVALuna2:4725